All the lovely bad ones - Hahn, Mary Downing (Houghton Mifflin Harcourt, 2008)
Travis and his sister Corey decide to boost business at their grandmother's Vermont inn by staging a few "hauntings" that soon draw tourists from across the country, but when their antics awaken a dark force, they must find a way to put to rest the ghosts they have disturbed.